2013
DOI: 10.1128/aem.01382-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Key Enzymes involved in l -Glutamate Synthesis and Degradation in the Thermotolerant and Methylotrophic Bacterium Bacillus methanolicus

Abstract: bBacillus methanolicus wild-type strain MGA3 secretes 59 g/liter ؊1 of L-glutamate in fed-batch methanol cultivations at 50°C. We recently sequenced the MGA3 genome, and we here characterize key enzymes involved in L-glutamate synthesis and degradation. One glutamate dehydrogenase (GDH) that is encoded by yweB and two glutamate synthases (GOGATs) that are encoded by the gltAB operon and by gltA2 were found, in contrast to Bacillus subtilis, which has two different GDHs and only one GOGAT. B. methanolicus has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…It is unknown which of these pathways is employed by B. methanolicus for l ‐glutamate production. However, recent findings have demonstrated that overexpression of glutamate synthase and glutamate dehydrogenase in B. methanolicus MGA3 has no or a marginally positive effect on glutamate production , while overproduction of the native Odh protein led to a fivefold reduction in glutamate. Interestingly, Odh overexpression in an l ‐lysine‐overproducing B. methanolicus host resulted in a twofold increase in l ‐lysine production yield, suggesting that Odh activity plays an important role at the branching point between glutamate synthesis and the TCA cycle, eventually regenerating the l ‐lysine precursor molecule oxaloacetate .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is unknown which of these pathways is employed by B. methanolicus for l ‐glutamate production. However, recent findings have demonstrated that overexpression of glutamate synthase and glutamate dehydrogenase in B. methanolicus MGA3 has no or a marginally positive effect on glutamate production , while overproduction of the native Odh protein led to a fivefold reduction in glutamate. Interestingly, Odh overexpression in an l ‐lysine‐overproducing B. methanolicus host resulted in a twofold increase in l ‐lysine production yield, suggesting that Odh activity plays an important role at the branching point between glutamate synthesis and the TCA cycle, eventually regenerating the l ‐lysine precursor molecule oxaloacetate .…”
Section: Resultsmentioning
confidence: 98%
“…However, recent findings have demonstrated that overexpression of glutamate synthase and glutamate dehydrogenase in B. methanolicus MGA3 has no or a marginally positive effect on glutamate production , while overproduction of the native Odh protein led to a fivefold reduction in glutamate. Interestingly, Odh overexpression in an l ‐lysine‐overproducing B. methanolicus host resulted in a twofold increase in l ‐lysine production yield, suggesting that Odh activity plays an important role at the branching point between glutamate synthesis and the TCA cycle, eventually regenerating the l ‐lysine precursor molecule oxaloacetate . Combining these findings with the proteome data generated for the presence of Odh in this study suggests that the potential for amino acid production could differ on both carbon sources, with methanol being the more suitable substrate for the production of glutamate and mannitol being the preferred substrate for the accumulation of lysine.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, under tryptophan starvation, B. subtilis increased the expression of the trp operon (Tam et al, ). In addition, GdhA , GlnA , and GltA which have crucial roles in ammonium assimilation and l ‐glutamate metabolism, were increased in γ‐PGA medium‐cultured cells (Krog et al, ; Zhu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The cell debris was removed by centrifugation at 4 °C for 10 min at 8,000g. Measurement of GDH and OGDH activities was performed as described by Krog et al [11] with slight modifications. Briefly, the GDH assay mixture generally contained 100 mM glycine-KOH (pH 7.5), 200 mM L-glutamate, 10 mM MgSO 4 , and 0.2 mM NAD + ; the OGDH assay mixture generally contained 50 mM TrisHCl (pH 7.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…a Chromosome structures of deletion-carrying strains were analyzed by agarose gel electrophoresis of PCR products generated with primers RocROUT-F/RocROUT-R(lanes 1-3); with primers RocGOUT-F/RocGOUT-R (lanes 4-6); with primers OdhAOUT-F/OdhAOUT-R (7-9); with primers GudBOUT-F/GudBOUT-R (lanes[10][11][12]. M DNA marker, and the size of each band is reported on the left.…”
mentioning
confidence: 99%